OUTSOURCING TO INDIA - Sancheti, Mayur (2007)
Topic selected by me for dissertation is of outsourcing to India. Outsourcing is generally done from countries like United Kingdom and United States. I have discussed each and every aspect which is related to Outsourcing in detail.